THE ROLE OF PLACEMENT OF FUNDS TO DETERMINE MUQABALAH IN BAITUL TAMWIL MUHAMMADIYAH (BTM) - Usamah, Usamah (JURNAL LITBANG KOTA PEKALONGAN, 2015)
THE PURPOSE OF THIS STUDY WAS TO ANALYZE THE PLACEMENT OF FUNDS TO DETERMINE MUQABALAH IN BAITUL TAMWIL MUHAMMADIYAH (BTM). BTM PLACEMENTS INCLUDE: PLACEMENT OF FUND IN CENTRAL BTM, BTM PLACEMENTS WITH OTHER BANKS, SHARIAH FINANCING. THIS STUDY USED A SAMPLE 27 BTM. DATA TAKEN FROM THE FINANCIAL STATEMENTS OF BTM WHICH HAS BEEN PUBLISHED BY BTM FROM 2012- 2014. THE ANALYSIS TOOLS ARE PARTIAL HYPOTHESIS TEST (T TEST) AND MULTIPLE REGRESSION. THE RESULTS SHOWED THAT THE PLACEMENT OF FUND IN CENTRAL BTM AND PLACEMENTS OF FUND WITH OTHER BANKS MUQABALAH INFLUENCE ON BTM. SHARIAH FINANCING INFLUENCE HELD SIGNIFICANT NEGATIVE INFLUENCE ON MUQABALAH IN BAITUL TAMWIL MUHAMMADIYAH.